2019
DOI: 10.1038/s41467-019-12429-6
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-doped Prussian blue enhances photothermal clearance of Staphylococcus aureus and promotes tissue repair in infected wounds

Abstract: The application of photothermal therapy to treat bacterial infections remains a challenge, as the high temperatures required for bacterial elimination can damage healthy tissues. Here, we develop an exogenous antibacterial agent consisting of zinc-doped Prussian blue (ZnPB) that kills methicillin-resistant Staphylococcus aureus in vitro and in a rat model of cutaneous wound infection. Local heat triggered by the photothermal effect accelerates the release and penetration of ions into the bacteria, resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
190
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 379 publications
(195 citation statements)
references
References 40 publications
5
190
0
Order By: Relevance
“…Notably, the temperature of Fe 3 O 4 /CNT/Gent was higher than 50°C after MV irradiation for 5 min and then maintained below 55°C for another 15 min. During this course, the temperature is adjustable by controlling the MV power, so that minimal invasion of normal tissues and highly effective bacteria-killing can be achieved in a short time 12 . The synergistic effect of Gent and MCT has also been verified and is expressed by the combination index 38 , where the combined value is <1, indicating a strong synergy between Gent and MCT (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the temperature of Fe 3 O 4 /CNT/Gent was higher than 50°C after MV irradiation for 5 min and then maintained below 55°C for another 15 min. During this course, the temperature is adjustable by controlling the MV power, so that minimal invasion of normal tissues and highly effective bacteria-killing can be achieved in a short time 12 . The synergistic effect of Gent and MCT has also been verified and is expressed by the combination index 38 , where the combined value is <1, indicating a strong synergy between Gent and MCT (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In order to tackle the crisis of antibiotic resistance, both antibiotic-free and antibiotic-strengthening strategies are being developed, such as phototherapy and photo-assisted antibiotics therapy. However, owing to the poor penetration depth of near infrared light, such strategies are only viable for subcutaneous tumors 10,11 or wound infections 12 ; they are not suitable for treating deep tissue infection. Therefore, it is urgent to develop better therapies that can effectively treat deep osteomyelitis, including MRSA infections, with minimum antibiotic toxicity.…”
mentioning
confidence: 99%
“…The resulting local temperature increase was sufficient to eradicate ≈76% of P. aeruginosa bacteria and mitigate P. aeruginosa biofilm growth. Another recent study, also published in 2019, validated an exogenous antibacterial agent consisting of zinc-doped Prussian blue nanoparticles against the methicillin-resistant S. aureus in vitro and in a rat model for a cutaneous wound infection [77]. The authors demonstrated that the photothermally induced local heat, triggered by the irradiation at 808 nm and 1.2 W/cm 2 , accelerates the release and penetration of ions into bacteria, resulting in an alteration of the intracellular metabolic pathways and causing bacterial death without a systemic toxicity.…”
Section: Applications Of Other Types Of Nanoparticles For Photothermamentioning
confidence: 99%
“…More speci cally, the bacterial cells treated with qCQDs were disintegrated to different degrees, the cytoplasmic density of bacterial cells obviously decreased, and even the phenomenon of cavities and substance agglomeration occurred in the bacterial cells. And bacterial cells lost their integrity, causing irreversible damage to bacteria cells and resulting in death of bacteria 40,41 , which was completely different from the untreated bacteria. The morphology of the treated bacteria indicated that qCQDs had the signi cant destructive effects on the above six species of bacterial cells, con rming the killing effect of qCQDs on both gram-positive and gram-negative bacteria.…”
Section: Temmentioning
confidence: 99%